2000
DOI: 10.1046/j.1460-9568.2000.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of group III metabotropic glutamate receptors in visually responsive neurons of the rat superficial superior colliculus

Abstract: There is evidence from immunohistochemical and in situ hybridization studies for the presence of Group I, II and III metabotropic glutamate receptors (mGluRs) in the rat superficial superior colliculus (SSC). The purpose of this study was to investigate if manipulation of Group III mGluRs affects visual responses in the SSC. Drugs were applied by iontophoresis and single neuron activity was recorded extracellularly. L-AP4 (Group III agonist) resulted in a reduction of visual responses in most neurons, but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
3
19
0
1
Order By: Relevance
“…In birds and mammals, retinal input to the visual midbrain is primarily mediated by glutamate that acts on ionotropic and metabotropic receptors, and blocking of these interrupts retinotectal transmission (Canzek et al, 1981;Binns and Salt, 1994;Dye and Karten, 1996;Cirone and Salt, 2000). Because in our experiments the glutamate receptor blocker CNQX completely abolished cellular responses of SGC neurons, we conclude that synaptic transmission at the bottlebrush endings of SGC-I neurons is mediated by glutamate receptors.…”
Section: Glutamate Receptors Mediate Monosynaptic Retinal Inputsmentioning
confidence: 51%
“…In birds and mammals, retinal input to the visual midbrain is primarily mediated by glutamate that acts on ionotropic and metabotropic receptors, and blocking of these interrupts retinotectal transmission (Canzek et al, 1981;Binns and Salt, 1994;Dye and Karten, 1996;Cirone and Salt, 2000). Because in our experiments the glutamate receptor blocker CNQX completely abolished cellular responses of SGC neurons, we conclude that synaptic transmission at the bottlebrush endings of SGC-I neurons is mediated by glutamate receptors.…”
Section: Glutamate Receptors Mediate Monosynaptic Retinal Inputsmentioning
confidence: 51%
“…In the superficial SC, the modulation of PPD by DHPG is in line with an autoreceptor-dependent feedback mechanism as an effective way to regulate glutamate release and short-term plasticity. The enhancement of the threshold for glutamate release during periods of repetitive incoming signals has also been suggested for presynaptic group II/III mGluRs (Cirone & Salt, 2000;Pothecary et al, 2002). It therefore remains to be investigated whether different mGluRs act in parallel, or independently at a particular subset of synapses.…”
Section: Presynaptic Actionsmentioning
confidence: 99%
“…The superficial SC receives a direct input from the retina, with 490% of retinal ganglion cells projecting to this area in the rat (Dreher et al, 1985) and glutamate is the principle excitatory transmitter at these synapses (Binns & Salt, 1994;Platt & Withington, 1998). Recently, studies on the function of mGluRs in the SC have demonstrated the contribution of group II/III receptors to visual processing (Cirone & Salt, 2000;Pothecary et al, 2002). Activation of group I mGluRs leads to an inhibition of visual responses by the agonist DHPG in vivo, and this action may be mediated by mGluR1 (Cirone et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have revealed very specific regional and cellular localisations [Nusser et al, 1994;Ohishi et al, 1994;Romano et al, 1995;Shigemoto et al, 1996;Petralia et al, 1996;Lujan et al, 1997;Mineff and Valtschanoff, 1999;Jia et al, 1999], including localisation on glial cells and axons [Ohishi et al, 1994;Jeffery et al, 1996;Petralia et al, 1996;Li et al, 1997;Mineff and Valtschanoff, 1999]. Interestingly, some mGlu receptors have been located in extrasynaptic locations or in the periphery of synapses [Nusser et al, 1994;Lujan et al, 1997], and this has led to the suggestion that they may be activated by glutamate A spilling over from synapses, and that this may occur during periods of intense or high frequency synaptic activity [Scanziani et al, 1997;Rusakov and Kullmann, 1998;Mitchell and Silver, 2000;Dube and Marshall, 2000], as may occur in vivo [Cirone and Salt, 2000]. Whether such mechanisms occur in nociceptive systems seems probable, but remains to be determined.…”
Section: Synaptic Location and Functional Possibilitiesmentioning
confidence: 99%